Substrate effect on band bending of MoSe₂ monolayer near mirror-twin domain boundaries - Yuan, Mengfei (2023)
Band bending near mirror twin domain boundaries (MTBs) in a MoSe2 monolayer grown on different substrates, i.e., highly oriented pyrolytic graphite (HOPG), graphene-on-SiC, and crystalline Au(110), is investigated by low temperature scanning tunneling microscopy/spectroscopy. Upshift bending of the valence band edge near MTB is observed on both graphene and HOPG substrates, whereas a downshift bending is found on Au(110). For the former, the magnitudes of bending are different. This is explained based on the static charge model, where an accumulative charge exists at MTBs due to both the electrical dipole discontinuity across the MTB as well as charge transfer between the substrate and MoSe2 epilayer. The relevance of the static electric model is further affirmed by noting a geometric effect on the band bending, where it is asymmetric across the vertex of an MTB loop.